Hereditary gingival fibromatosis - Dhadse, Prasad Vijayrao (Medknow Publications & Media Pvt Ltd, 2012)
Hereditary gingival fibromatosis is a rare benign oral condition characterised by slow and progressive enlargement of both maxillary and mandibular attached gingiva. It may develop as an isolated disorder but can feature along with a syndrome. A case of 12 year old female child who presented with generalised severe gingival overgrowth, involving both the arches and covering almost the entire dentition, and had all the teeth remaining invisible within the confinement of gingival tissues. The excess gingival tissue, in this non-syndromic case was removed by conventional gingivectomy using local as well as general anaesthesia. The post-operative result was uneventful and the patient appearance improved considerably. Good aesthetic result was achieved to allow patient to practice oral hygiene measures. After treatment regular recall visits are necessary in order to evaluate oral hygiene and stability of periodontal treatment.